(untitled) (Research, Society and Development, 2026)
The pandemic context, marked by social isolation, financial insecurity, social pressure, and fear of COVID-19, generated a significant increase in stress, anxiety, and depression, conditions that directly affect oral health, especially in the development of bruxism and temporomandibular disorders. These disorders, associated with emotional conditions, affect the quality of life of the population and can cause muscle pain, tooth wear, and functional limitations. This study reviews the literature to assess the increase in cases of bruxism and temporomandibular disorders (TMD) as a result of the psychological problems caused by the COVID-19 pandemic. The bibliographic research was conducted between January and February 2025, with data collected from databases such as LILACS, BVS, PubMed, and SciELO, using the descriptors "bruxism," "TMD," "COVID-19," and "incidence." A total of 31 articles were initially selected, but after applying inclusion and exclusion criteria, 15 were chosen. The analyzed studies show that the worsening of the population’s emotional state during the COVID-19 pandemic had a direct impact on oral health, with an increased prevalence of bruxism and TMD symptoms, especially among those who experienced higher levels of anxiety and depression. Among students and healthcare professionals, an increasing incidence of sleep and awake bruxism was observed, both related to stress. It is concluded that the COVID-19 pandemic directly exacerbated factors such as anxiety, stress, and bruxism (psychosocial factors), resulting in a higher incidence of bruxism and TMD, highlighting the need for preventive and treatment interventions for these problems.